CULTURAL APPROACH TO ANALYZING STATE BUILDING IN THE MIDDLE EAST - Osadcha, Y. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
The article examines the characteristics of the cultural approach to describing Middle East politics and the process of state building. Both – advantages and disadvantages of this approach are analyzed. The author states that religion itself cannot be a major factor, which determines the development and internal structure of political institutions as well as the probability of democratization of the Middle Eastern regimes.